Control of shunt active power filter for power quality improvements with PV system using MPC approach - Heguig, Larouci; Mesbahi, Nadhir; Guettaf, Yacine (International Journal of Power Electronics and Drive Systems (IJPEDS), 2025)
The major issue facing the electrical grid is the excessive use of non-linear loads, which pull distorted (non-sinusoidal) current from the grid. Considering this constraint, the objective is to remove any harmonic currents from the grid. The active filtering method has been selected, particularly focusing on the use of the shunt active filter, which provides numerous benefits. Therefore, in order to achieve effective harmonic compensation, a suitable and resilient control system is necessary for the shunt active filter. The system outlined in this study comprises a photovoltaic generator connected to the distribution electrical grid via a shunt active filter in order to simultaneously ensure the injection of renewable power generated by the photovoltaic generator into the grid and the improvement of the electrical energy quality. In this study, a model predictive current is introduced for shunt active power with fuzzy logic control to optimize the tracking of the maximum power point for the photovoltaic generator. The system was studied under various conditions, and the simulation was carried out using MATLAB/Simulink on the entire system.